Effect of Iodothyronines on Thermogenesis: Focus on Brown Adipose Tissue - Cioffi, Federica; Gentile, Alessandra; Silvestri, Elena; Goglia, Fernando; Lombardi, Assunta (Frontiers in Endocrinology, 2018)
Thyroid hormones (THs) significantly influence energy expenditure by affecting the activity of metabolic active tissues, among which mammalian brown adipose tissue (BAT) plays a significant role. For long time, the modulation of BAT activity by 3,3’,5-triiodo-L-thyronine (T3) has been ascribed to its direct actions on this tissue; however, recent evidence indicates that T3, by stimulating specific brain centers, activates the metabolism of BAT via the sympathetic nervous system. These distinct mechanisms of action are not mutually exclusive. New evidence indicates that 3,5-diiodo-L-thyronine (3,5-T2), a thyroid hormone derivative, exerts thermogenic effects, by influencing mitochondrial activity in metabolically active tissues, such as liver, skeletal muscle and BAT. At the moment, due to the absence of experiments finalized to render a clear cut discrimination between peripheral and central effects induced by 3,5-T2, it is not possible to exclude that some of the metabolic effects exerted by 3,5-T2 may be mediated centrally. Despite this, some evidence suggests that 3,5-T2 plays a role in adrenergic stimulation of thermogenesis in BAT. This mini-review provides an overview of the effects induced by T3 and 3,5-T2 on BAT thermogenesis, with a focus on data suggesting the involvement of central adrenergic stimulation. These aspects may reveal new perspectives in thyroid physiology and in the control of energy metabolism.